(untitled) (European Journal of Pedagogical Initiatives and Educational Practices, 2025)
The First World War (1914-1918) was a pivotal conflict that significantly altered the course of history. This paper examines the multifaceted causes and far-reaching consequences of the war. The long-term factors contributing to the war included militarism, which led to an arms race among European powers; imperialism, which fueled competition for global dominance; nationalism, particularly in the Balkans, which led to ethnic tensions; and a complex web of alliances that set the stage for a larger conflict. The assassination of Archduke Franz Ferdinand in Sarajevo served as the immediate spark, triggering a chain reaction that rapidly escalated into a world war. The consequences of the war were wide-ranging: politically, it resulted in the collapse of the Austro-Hungarian, Ottoman, German, and Russian empires and the creation of new nation-states. Economically, the war left Europe deeply indebted, leading to long-term financial instability, while the Treaty of Versailles imposed punitive measures on Germany, sowing the seeds for future conflict. Socially, the war caused immense human loss, contributing to a changing social fabric, with shifts in gender roles, the rise of women’s participation in the workforce, and widespread trauma. The war also provided fertile ground for the rise of totalitarian regimes, including fascism and communism, setting the stage for ideological struggles that would define the interwar period. This study delves into both the proximate and underlying causes of World War I, as well as its transformative consequences, offering insight into how the war reshaped global politics, economies, and societies in the 20th century.